2004
DOI: 10.4314/sajrs.v26i2.25899
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of the job security of professional sports coaches in South Africa

Abstract: This paper presents the results of a study targeted at human resources managers and professional sports coaches at sport organisations affiliated to the South African Sports Commission, in all nine provinces of South Africa. It focuses specifically on the job security of professional sports coaches. The methodology involved an extensive literature survey, structured in-depth interviews and the administration of 900 structured questionnaires. The analysis of data revealed that most of the professional sports co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This finding is not new within the South African context. Surujlal et al 17 reported that there was a high turnover of sports coaches. Therefore, the fact that coaches are dismissed irrespective of their winning performance is a matter of concern in the country.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is not new within the South African context. Surujlal et al 17 reported that there was a high turnover of sports coaches. Therefore, the fact that coaches are dismissed irrespective of their winning performance is a matter of concern in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Singh and Moodley (2001) expressed concern that the employment contracts of many coaches do not promise security or stability for coaches resulting in them becoming insecure in their jobs. Surujlal, Singh and Hollander (2004) found that despite the fact that most coaches were consulted in the drawing up of their contracts, most contracts were to the advantage of one party, namely the employer. Respondents in the study commented that while every attempt is made to employ coaches on a full time basis, this is not always possible.…”
Section: Contractsmentioning
confidence: 99%
“…Today sport coaches demand more of their jobs and respond favourably to management activities that give them greater control of their lives (Ivancevich, 1998). Previous studies on the job of coaches by Li (1993), Chelladurai & Ogasawara (2003), Surujlal (2004) and Surujlal et al (2004) indicate that sport coaches experience, on average, moderate levels of job satisfaction. This has become problematic in sport organisations in South Africa (SA) where the recognition and acceptance of the importance of sport coaching in the past was based on the notion of developing healthy participants (Singh & Moodley, 2001).…”
Section: Problem Statementmentioning
confidence: 92%